Arresting the Malaysian judiciary’s ambivalent syndrome concerning the quantum of proof in allegations of fraud in civil cases – in the interest of certainty in the law - Shair Mohamad, Mohd Akram; Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (International Organization Center of Academic Research (OCERINT) Publishing, 2017)
It has been settled law in Malaysia that the quantum of proof in civil courses is on a balance of probabilities. Even if the allegation is fraud, still the balance of probability standard applies. Though the civil court when considering a charge fraud will naturally require for itself a higher degree of probability than that which it would require when negligence or breach of contract is established. It does not adopt so high a degree as a criminal court, but still it does require a degree of probability which is commensurate with the occasion. However, this traditional position has been departed from a series of apex court decisions which had held that in civil cases the quantum of proof required in allegations of fraud is beyond a reasonable doubt. The Apex court has even gone to the extent of pronouncing that this is the common law of Malaysia. Then there is another view which enunciates that the quantum of proof required in allegations of fraud in civil cases will depend on the nature of fraud. If the nature of the fraud alleged is criminal, than the amount to evidence required to prove that allegation is the criminal standard of beyond reasonable doubt. If the nature of fraud is civil, then civil standard of balance of probabilities suffices. This ambivalent judicial attitude has now been compound by a recent 2015 apex court decision, that all is required to prove fraud is just on a balance of probabilities, irrespective of the nature of the allegation. The paper seeks to analyse the law on this matter by looking at the judicial attitudes of other common law jurisdictions such as Australia, Singapore and the United Kingdom and suggest that the Malaysian judiciary adopt a consistent approach that will be a conduce clarity, instead of creating confusion in this critical area of the law.